Pengaruh Sistem Pengendalian Internal, Sistem Keuangan Desa, Partisipasi Masyarakat Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Desa Tahun 2025 - Enggar Priska; Maya Widyana Dewi; Sri Laksmi Pardanawati (Jurnal Akuntansi dan Pajak, 2027)
This study aims to determine the influence of the Village Financial System, Internal Control, Utilization of Information Technology, and Community Participation on the Accountability of Village Fund Management in Ngemplak District. This study uses a quantitative approach. The study population consisted of all village officials in Ngemplak District, totaling 114 respondents. The sampling technique used was a purposive sampling method with 74 respondents. The data source for this study was primary data using a questionnaire. This study employed data analysis methods including descriptive statistics, validity tests, reliability tests, and classical assumption tests. Hypothesis testing included multiple linear regression analysis, F tests, t tests, and the coefficient of determination (R2). The results of this study indicate that the Village Financial System and Utilization of Information Technology have a positive and significant effect on the Accountability of Village Fund Management, while Internal Control and Community Participation do not have a positive and significant effect on the Accountability of Village Fund Management. Keywords: Accountability of Village Fund Management, Community Participation, Internal Control, Utilization of Information Technology, Village Financial System